On the issue of substantiating mathematical models of technical and economic indicators of gas distribution systems under conditions of uncertainty - Paleyev, A.; Kotukh, V.; Husieva, Y.; Paleyeva, K. (Radiotekhnika, 2025)
The issues of reliability of gas transportation systems and their functioning in conditions of uncertainty are very relevant today. This is due to the fact that in the last few years the political and economic situation in the country has changed significantly, the quantitative and qualitative composition of the population, and logistics routes have changed. There has also been a rapid growth in modern technology and equipment. Because of these factors, it is necessary to change the approach to the structure of the entire heat and power supply system as a whole, to the choice of energy carrier, as well as to the elements of gas transportation systems, for example, gas distribution systems. When solving these problems, certain problems arise that are difficult or impossible to solve using traditional methods of optimization calculations. One of the ways to reliably provide energy resources to end consumers is the decentralization of such systems, the construction of new ones, reconstruction and maintenance of the reliable functioning of individual elements and components. The purpose of this work is to consider ways to improve the efficiency of design, redesign and reconstruction of gas distribution systems and to substantiate mathematical models of technical and economic indicators of gas distribution systems under conditions of uncertainty. The article explores the issue of determining the optimal construction sequence and the procedure for putting into operation a new system (or reconstruction of an existing system), in which the total costs during construction (reconstruction) would be minimal. At the same time, determining the priority of construction (reconstruction) of gas distribution systems should be carried out taking into account the characteristic features, including taking into account the directions and areas of consumer location, types and existing energy distribution schemes. A mathematical model of the heat and power supply system for a certain territorial unit (region, settlement, district, etc.) or a single group of consumers is also given. Transportation of energy carriers is carried out through “logistics” points. This model allows for comparison of different (from the point of view of routing) schemes for providing a territorial unit with the same energy carrier, provided that they have different energy carriers. The issues discussed in the article will make it possible to further improve the process of creating and operating models, methods and information technologies for monitoring the condition of gas distribution systems under conditions of uncertainty.